lncRNA GAS5 suppression of the malignant phenotype of ovarian cancer via the miR-23a-WT1 axis - Zhou, Li; Jiang, Hongye; Lin, Lin; Li, Yinguang; Li, Jie (Annals of translational medicine, 2023)
Growth arrest-specific 5 (GAS5) is a long noncoding RNA (lncRNA) that regulates cell viability. GAS5 lncRNA has been shown to decrease colorectal and breast cancer carcinogenesis. Although the function and mechanisms related to lncRNA GAS5 in the development of ovarian cancer (OC) remains unclear. The goal of this study was to clarify the essential functions of lncRNA GAS5 in regulating OC progression and its underlying mechanism. Relative levels of lncRNA GAS5 in OC and normal ovarian tissues were identified by quantitative real-time polymerase chain reaction (qRT-PCR). The regulatory effects of lncRNA GAS5 on the proliferation and apoptosis of SK-OV-3 cells were evaluated. Moreover, bioinformatics tools were used to predict a novel target [microRNA (miRNA)] of lncRNA GAS5. To explore the key functions of the lncRNA GAS5/miRNA-23a/WT1 regulatory loop in mediating OC progression, we performed functional experiments and a dual-luciferase reporter (DLR) gene assessment. Downregulation of lncRNA GAS5 was found in tissues of OC, which was positively correlated with a poor prognosis. In addition, SK-OV-3 cells with a lower expression of lncRNA GAS5 and accelerated cancer cell migration demonstrated a lower percentage of apoptosis in experiments. It was demonstrated that lncRNA GAS5 acts as a molecular sponge for miR-23a in OC cells. Additionally, WT1 was detected as a miR-23a target gene in OC cells, and through sponging miR-23a, lncRNA GAS5 positively regulated WT1 expression. Rescue tests demonstrated that enhancing the outputs of the miR-23a-WT1 axis reversed the impacts of lncRNA GAS5 silencing on cell proliferation and apoptosis in OC. The lncRNA GAS5/miR-23a/WT1 cascade was found participate in the progression of OC. lncRNA GAS5 also decreases OC progression by upregulating WT1 and attenuating miR-23a, suggesting that it could be an advantageous therapeutic target for OC intervention.